Análise dos fatores que influenciam a intenção de compra de imóveis - Pessoa, Ciana Celita (My University, 2023)
Construction market has been growing in the last decades and to understand costumer behavior has become a subject of great ambition in the organizational context, as well as a great challenge for organizations. Therefore, it knows relevant aspects at consumer when choosing a property becomes a competitive advantage in the real estate market. From this, this study aims to analyze which attributes are valued, in the context of durable goods with a focus on the acquisition of real estate, in the light of the constructs: perceived quality, trust, perceived usefulness, affective identification and purchase intention. To carry out the analysis, multivariate analysis was used, and more specifically Exploratory Factor Analysis (EFA), generating eight attributes that grouped the 47 variables, which represented the attributes identified in the researched literature: Responsiveness, Tangible Quality, Reliability, Guarantee, Responsiveness, Purchase Intention, Affective Identification and Perceived Usefulness. Finally, the objective was fulfilled by identifying which attributes are important for the consumer's decision-making process in the civil construction sector, based on the studied sample, contributing with guidelines that allow the increase in the items valued by them in the sector under analysis. [resumo fornecido pelo ator]
Com a crescente expansão do setor de construção civil nas últimas décadas, entender o comportamento de consumo passou a ser tema de grande ambição no contexto organizacional, bem como, um grande desafio para as organizações. Portanto, conhecer quais aspectos são relevantes ao consumidor na escolha de um imóvel se torna uma vantagem competitiva no mercado imobiliário. A partir disso, este estudo tem como objetivo analisar quais atributos são valorizados pelo consumidor, no contexto com enfoque na aquisição de imóveis, a luz dos construtos: qualidade percebida, confiança, utilidade percebida, identificação afetiva e intenção de compra. Para realização da análise foi utilizada análise multivariada e mais especificamente a Análise Fatorial Exploratória (AFE), gerando oito fatores que agruparam as 47 variáveis, que representavam os atributos identificados na literatura pesquisada: Capacidade de resposta, Qualidade tangível, Confiabilidade, Garantia, Responsividade, Intenção de Compra, Identificação Afetiva e Utilidade percebida. Por fim, o objetivo se cumpriu ao identificar quais atributos são importantes para o processo de tomada de decisão do consumidor no setor da construção civil, com base na amostra estudada, contribuindo com diretrizes que possibilitem o incremento nos itens valorados por estes no setor em análise. [resumo fornecido pelo ator]
Keywords: Administração; Compra e venda de bens imóveis; Comportamento do consumidor; Mercado imobiliário; Bens imóveis; Management; Vendors and purchasers; Consumer behavior; Real estate business; Real property